Amino acid oxidation and alanine production in rat hemidiaphragm in vitro. Effects of dichloroacetate. - Palmer, T N (1984)
Dichloroacetate (an activator of pyruvate dehydrogenase) stimulates 14CO2 production from [U-14C]glucose, but not from [U-14C]glutamate, [U-14C]aspartate, [U-14C]- and [1-14C]-valine and [U-14C]- and [1-14C]-leucine. It is concluded (1) that pyruvate dehydrogenase is not rate-limiting in the oxidation to CO2 of amino acids that are metabolized to tricarboxylic acid-cycle intermediates, and (2) that carbohydrate (and not amino acids) is the main carbon precursor in alanine formation in muscle.